Acting for the camera : back to one - Stone, Peter Allen (New York: Routledge, 2021)
"Acting for the Camera: Back to One is a "how to" book with simple, practical steps to achieve a professional performance on camera. The book focuses on four distinct areas: how to prepare the character and bring them to life, how to execute the technical responsibilities that will assist the editor in creating the on-camera performance in post-production, tips from industry professionals, and how to create effective self-tape auditions. Part One: The Character's World is packed with tools to analyze the script and fully prepare the character before arriving on set. Part Two: The Actor's World focuses on developing technical acting skills for the camera that assist the pre- and post-production teams to create a dynamic on-screen performance. In Part Three: The Professional World industry professionals provide tips from inside the Film/TV audition room and how to navigate a career in the acting business. The final section, Part Four: Self-Tape Like a Pro, outlines how to build a self-tape studio in the privacy of your own home and submit high-quality self-tape auditions that will help you stand out from the competition. Written for students enrolled in Acting for the Camera courses, Acting for the Camera: Back to One explores techniques that can be practiced and mastered by actors of all levels, from the moment they audition for the part through to when they hear that director call "cut!""--
Introduction: Back to one -- Preparation -- Breaking down the script : the value of beats -- Given circumstances & relationships : bring life on -- Objective : make it about the other character -- Actions : river vs pond acting -- Obstacles : character problems are actor gifts -- Character notebook : mapping out the role -- Acting for the camera -- Frame : play the piece of pie -- Size : scaling the performance -- Action : what do I do now? -- Art of the reaction : help the editor make you look great -- Hitting the mark : skill vs talent -- Physical continuity : acting with props -- Voice : play the distance -- Camera time : work with the camera -- The final beat : focal shifts and cutting points -- Auditioning -- Learn from the pros -- Ten audition tips to help you win -- Industry interviews -- Today's actor : production skills -- Studio space : find it now -- Lights, camera, & sound : building an affordable studio -- Filming : slating, intimacy, props, the reader -- Editing & submitting : it's an audition not a movie -- Final thoughts.
Includes index.
Keywords: Motion picture acting; Television acting; Acting; Acting